2017
DOI: 10.3390/nu9060575
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Qualitative Perspectives on Child Asking for Fruit and Vegetables

Abstract: Children can influence the foods available at home, but some ways of approaching a parent may be better than others; and the best way may vary by type of parent. This study explored how parents with different parenting styles would best receive their 10 to 14 years old child asking for fruits and vegetables (FV). An online parenting style questionnaire was completed and follow-up qualitative telephone interviews assessed home food rules, child influence on home food availability, parents’ preferences for being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…In general, when a child asks the parent for a specific vegetable or fruit, they tend to comply with this request [52]. But for children aged 2–5 years, it was observed that food product choices based on their desire may decrease their preference for healthy food products, including vegetables, as they would rather ask about products other than vegetables [53].…”
Section: Discussionmentioning
confidence: 99%
“…In general, when a child asks the parent for a specific vegetable or fruit, they tend to comply with this request [52]. But for children aged 2–5 years, it was observed that food product choices based on their desire may decrease their preference for healthy food products, including vegetables, as they would rather ask about products other than vegetables [53].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the finding of Joanna et al (2016) who found that children’s preferences have a strong impact on mothers’ choices in the supermarket. Children’s preferences have been associated with mothers’ feeding style (Lively et al , 2017) and parenting style (Beltran et al , 2017), these styles of feeding and parenting may warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Los estilos parentales generales, estilos alimentarios y prácticas de alimentación tienen una importancia fundamental sobre la dieta y el comportamiento alimentario de los hijos (Norman et al, 2018;Beltran et al, 2017). Los estilos parentales son comportamientos, creencias y actitudes que los padres aplican en su crianza de los hijos, habiéndose descrito cuatro estilos principales: autoritativo, autoritario, permisivo y negligente (Sokol et al, 2017).…”
Section: Estilos Parentalesunclassified